A rare combination of acute myeloid leukemia with Vit B12 deficiency: Case report. (September 2022) - Kitaz, Mohammad Nour; Zazo, Rama; Alsabbagh, Muhammad; Diabi, Muhammad; Alnahar, Salam; Chammout, Anwar
Abstract: Introduction and importance: Acute myeloid leukemia (AML) is a malignant disease with several risk factors from hematologic disorders, which almost presents as anemia. AML is characterized by the presence of myeloblast in the blood picture. On the other hand, macrocytic anemia characterized by the presence of megaloblastic marrow morphology. We are presenting a rare case of combined Acute myeloid leukemia with macrocytic anemia. Case presentation: A 45 years old married woman was admitted for hyperthermia, dysuria, and chills. She had suffered from general malaise, weakness, and myalgia for two months. In her laboratories, the peripheral blood sample showed: HGB 26.1% (5.6 g/dL), RBCs 1.4 M/μL, WBC 13.3 K/μL. The blood smear showed megaloblastic features, so she was diagnosed with macrocytic anemia, and the treatment was blood transfusion, antibiotics, and muscular Vit B12. After one month, the peripheral blood sample showed an elevation of WBC, the bone marrow aspiration showed myeloblast infiltration represents 60% of the total events, and the flow cytometry for the bone marrow aspiration agrees with Acute Myeloblastic leukemia with Maturation M2 (AML-M2). Clinical discussion: The incidence of macrocytic anemia and leukemia in one patient is infrequent, case reports give scarce information concerning a potential increased occurrence of leukemia in patients putting up with macrocytic anemia. Several theories discussed the reasons for the association of the two conditions. Conclusion: we need more research on similar cases to identify the pathological mechanism. Highlights: The incidence of macrocytic anemia and leukemia in one patient is infrequent. The theory of somatic mutation could explain the development of leukemia in patients with macrocytic anemia. Pure chance is the most acceptable theory in the light of the low incidence of the Combination. Vitamin B12 and folic acid could correct the abnormal response of granulocytic. The vitamin B12 treatment Support leukemia.